Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0021569
|View full text |Cite
|
Sign up to set email alerts
|

BH3‐only Proteins

Abstract: The deregulation of programmed cell death, apoptosis, is a major contributor to the development of cancer and can impair the response of tumour cells to anticancer therapy. The Bcl‐2 family of proteins are critical regulators of apoptosis. BH3 (Bcl‐2 homologous 3)‐only proteins are pro‐apoptotic members that share with each other and the wider Bcl‐2 family only the BH3 domain that is critical for their killing capacity. These BH3‐only proteins promote cell death by directly or indirectly activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In human tumors, mutations of PUMA or NOXA have rarely been documented, but loss of heterozygosity has been described for NOXA and multiple modes of abnormal reduction, including epigenetic silencing, overexpression of inhibitory microRNA, and deletion have been described for PUMA and BIM (reviewed in Happo et al 52 ). Our data indicate that inactivation of all 3 genes may result in drug resistance as severe as that seen for the loss of p53 or overexpression of Bcl-2 18 and thereby demonstrate the importance of understanding the status of these 3 BH3-only proteins for the prediction of drug response.…”
Section: Discussionmentioning
confidence: 99%
“…In human tumors, mutations of PUMA or NOXA have rarely been documented, but loss of heterozygosity has been described for NOXA and multiple modes of abnormal reduction, including epigenetic silencing, overexpression of inhibitory microRNA, and deletion have been described for PUMA and BIM (reviewed in Happo et al 52 ). Our data indicate that inactivation of all 3 genes may result in drug resistance as severe as that seen for the loss of p53 or overexpression of Bcl-2 18 and thereby demonstrate the importance of understanding the status of these 3 BH3-only proteins for the prediction of drug response.…”
Section: Discussionmentioning
confidence: 99%
“…2). The mutual cross-talk between p53 and PUMA is an excellent mechanism for preventing the growth and division of abnormal cells, thereby protecting them against the development of cancer [51]. p53-dependent activation of PUMA function occurs when cells receive a wide variety of stress signals.…”
Section: Puma In P53-dependent Apoptosismentioning
confidence: 99%
“…In several studies of urban particulate matter, PAHs content was negatively associated with particle-induced production of proinflammatory cytokines and chemokines in THP-1 cells, [57] in RAW 264.7 cells (a mouse ascites fluid macrophage-like cell line), [58] and in mouse lungs. [59,60] Jalava et al [58] suggested that PAHs induce immunosuppression and low cytokine production. For in vivo exposure of carbonaceous particles via instillation, Stoeger et al [61] found that the fraction of soluble organics was negatively associated proinflammatory response.…”
Section: Inflammatory Responsementioning
confidence: 99%